A case of systemic polyarteritis nodosa involving bronchial artery - Lee, Y.J.; Park, S.S.; Kim, et al., S.Y. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Polyarteritis nodosa(PAN) is a systemic necrotizing vasculitis involving predominantly mediumsized muscular arteries. It commonly involves skin, kidney, cardiovascular system, gastrointestinal system, and neurological system. But bronchial artery involvement of PAN is rarely identified. We report a case of PAN with initial presentation of hemoptysis. On admission, chest radiograph and chest CT angiography revealed no focus of bleeding. Angiography showed a bronchial artery aneurysm and multiple arterial aneurysms in both renal, hepatic, mesenteric and branches of small bowel arteries.These findings were compatible with the diagnosis of PAN. The patient was started on steroid and cyclophosphamide.